Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.chiabu.2016.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Delay in disclosure of non-parental child sexual abuse in the context of emotional and physical maltreatment: A pilot study

Abstract: The present pilot study sought to identify predictors of delays in child sexual abuse (CSA) disclosure, specifically whether emotional and physical abuse by a parental figure contributes to predicting delays over and above other important victim factors. Alleged CSA victims (N=79), whose parental figures were not the purported sexual abuse perpetrators, were interviewed and their case files reviewed, across two waves of a longitudinal study. Regression analyses indicated that experiencing both emotional and ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 51 publications
1
26
0
1
Order By: Relevance
“…In these adult samples, participants have described that as children they were afraid of revenge or of being punished or blamed for what had happened (e.g., Anderson, Martin, Mullen, Romans, & Herbison, 1993;Browne & Finkelhor, 1986;Conte & Berliner, 1988;Herman & Hirschman, 1981;Palmer et al, 1999;Wyatt & Newcomb, 1990). A recent pilot study by Tashjian, Goldfarb, Goodman, Quas, and Edelstein (2016) showed that having also experienced emotional or physical abuse by a parental figure may delay the disclosure.…”
Section: Retrospective Surveysmentioning
confidence: 99%
See 2 more Smart Citations
“…In these adult samples, participants have described that as children they were afraid of revenge or of being punished or blamed for what had happened (e.g., Anderson, Martin, Mullen, Romans, & Herbison, 1993;Browne & Finkelhor, 1986;Conte & Berliner, 1988;Herman & Hirschman, 1981;Palmer et al, 1999;Wyatt & Newcomb, 1990). A recent pilot study by Tashjian, Goldfarb, Goodman, Quas, and Edelstein (2016) showed that having also experienced emotional or physical abuse by a parental figure may delay the disclosure.…”
Section: Retrospective Surveysmentioning
confidence: 99%
“…The aim of the present study was to contribute to the scientific literature on CSA disclosure by exploring the disclosure rates and factors associated with disclosure in a large population-based sample of children (the Finnish Child Victim Survey). The focus was specifically on factors associated with disclosing CSA to adults (parents and/or authorities), since adults tend to serve as intermediaries regulating the access to getting help and initiating investigation processes (Tashjian et al, 2016). Examining disclosure as a part of the national Victim Survey enabled us to consider also the widely ignored theme of experiencing violence at home and how it might influence disclosing CSA to adults (Tashjian et al, 2016).…”
Section: The Present Studymentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been shown that traumatic childhood events, such as the abuse and ignorement of physical, emotional, and sexual could affect the EF during early adulthood (De Prince et al, 2009;Wamser-Nanney and Sager, 2018;Tashjian et al, 2016). Individuals who have experienced maltreatment might have behavioral problems, decreased cortical brain volumes, and deficits in decision-making ability and cognitive performance (Cowell et al, 2015;Hanson et al, 2015;Polderman et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…ÇCÝ durumunda çoðunlukla somut kanýtlarýn býrakýlmamasý ve cinsel eylemlerin gizli doðasý nedeniyle bu istismarý açýða çýkarmanýn yükü çocuklara býrakýlmaktadýr (17). Alaggia (10), çocuklarýn cinsel istismarý açýklama yollarýna iliþkin yaptýðý araþtýrmanýn bulgularý ile diðer araþtýrma bulgularýný bütünleþtirerek dört kategori taným-lamýþtýr.…”
Section: çOcuðun Cinsel ýStismarý Açýklama Yollarýunclassified